"If you don't believe it, it won't help you": use of bush medicine in treating cancer among Aboriginal people in Western Australia - Shahid, Shaouli; Bessarab, Dawn; Thompson, Sandra; Bleam, R. (BioMed Central, 2010)
Background. Little is known about the use of bush medicine and traditional healing among Aboriginal Australians for their treatment of cancer and the meanings attached to it. A qualitative study that explored Aboriginal Australians' perspectives and experiences of cancer and cancer services in Western Australia provided an opportunity to analyse the contemporary meanings attached and use of bush medicine by Aboriginal people with cancer in Western Australia. Methods. Data collection occurred in Perth, both rural and remote areas and included individual in-depth interviews, observations and field notes. Of the thirty-seven interviews with Aboriginal cancer patients, family members of people who died from cancer and some Aboriginal health care providers, 11 participants whose responses included substantial mention on the issue of bush medicine and traditional healing were selected for the analysis for this paper.Results. The study findings have shown that as part of their healing some Aboriginal Australians use traditional medicine for treating their cancer. Such healing processes and medicines were preferred by some because it helped reconnect them with their heritage, land, culture and the spirits of their ancestors, bringing peace of mind during their illness. Spiritual beliefs and holistic health approaches and practices play an important role in the treatment choices for some patients. Conclusions. Service providers need to acknowledge and understand the existence of Aboriginal knowledge (epistemology) and accept that traditional healing can be an important addition to an Aboriginal person's healing complementing Western medical treatment regimes. Allowing and supporting traditional approaches to treatment reflects a commitment by modern medical services to adopting an Aboriginal-friendly approach that is not only culturally appropriate but assists with the cultural security of the service.